Geography - Owen, Andy; Coleman, Gregg; Davis, Val; Digby, Bob (Dynamic learning, 2020)
Develop your students' subject knowledge and skills using the second edition of the WJEC GCSE (9-1) Geography A Student book. With modernised and engaging case studies, new practice questions help students as they progress through their GCSE, providing additional opportunities to practice higher tariff exam style questions. The new Key Terms boxes provide students with concise and easy to understand definitions of key geographical terms. - Contains coherent coverage of every core and optional theme in a single volume, with clear explanations of key concepts throughout - Engages and challenges students of all abilities with an exciting, thematic approach, brought to life by Welsh, UK and international place references - Improves students' ability to interpret, analyse and evaluate geographical information through practical, skills-focused activities that involve data, maps and photographs - Boosts candidates' confidence approaching examination by providing numerous learning opportunities for each assessed theme - Enables effective differentiation with enquiry tasks designed to stretch higher-ability students and encourage independent research.